New occurrence records of Mico acariensis (Primates, Callitrichidae) - Noronha, Maurício Almeida; Silva Jr, José Sousa; Spironello, Wilson Roberto; Ferreira, Dayse Campista (Neotropical Primates, 2007)
No abstract